2021
DOI: 10.12998/wjcc.v9.i18.4559
|View full text |Cite
|
Sign up to set email alerts
|

Expected outcomes and patients’ selection before chemoembolization—“Six-and-Twelve or Pre-TACE-Predict” scores may help clinicians: Real-life French cohorts results

Abstract: BACKGROUND Careful selection of hepatocellular carcinoma (HCC) patients prior to chemoembolization treatment is a daily reality, and is even more necessary with new available therapeutic options in HCC. AIM To propose two new models to better stratify patients and maximize clinical benefit: “6 and 12” and “pre/post-TACE-predict” (TACE, transarterial chemoembolization). METHODS We evaluated and compared their performance in predicting overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, its utility in helping physicians in determining which HCC patients are not suitable for TACE is limited. Moreover, subsequent external validation studies showed that the “six-and-twelve” score had a lower prognostic ability, with AUROCs ranging from 0.59 to 0.699 ( 16 , 32 , 35 37 ), when compared to the original Wang et al ( 17 ) cohort (0.73).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its utility in helping physicians in determining which HCC patients are not suitable for TACE is limited. Moreover, subsequent external validation studies showed that the “six-and-twelve” score had a lower prognostic ability, with AUROCs ranging from 0.59 to 0.699 ( 16 , 32 , 35 37 ), when compared to the original Wang et al ( 17 ) cohort (0.73).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wang et al [ 26 ] developed an easy-to-use model, referred to as the "six-and twelve" score, which stratifies ideal TACE candidates based on the sum of tumor size and number of lesions. Unfortunately, the results of some external validation studies suggested that the model only has a modest predictive ability[ 27 , 28 ]. More recently, Han et al [ 29 ] developed a survival prediction model that assesses patients prior to initial TACE.…”
Section: Discussionmentioning
confidence: 99%
“…In the original study on the SAT, the score outperformed the BCLC classification and the ALBI score in predictive ability. In external validation studies, the C-Indexes for the SAT ranged between 0.60 and 0.70 ( 14 18 ). However, in all the validation studies, the predictive performance of the SAT was within the same range or somewhat below the performance of the BCLC and ALBI scoring systems ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…It sums the number of tumor nodes and tumor size to obtain a readily applicable stratification system. In the original study, the score showed promising performance, but in an external validation, contrary results were found for the prognosis prediction (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 87%